Britt Nicole [compact disc] - Britt Nicole (Capitol Christian Music Group, 2016)
The latest album from Britt Nicole features the high-energy tracks, catchy hooks, and top 40 beats that fans have come to expect, while sharing her consistent message of hope with existing fans and those to come.